Massive femur defect after Ewing's sarcoma resection reconstructed with a free vascularised fibular graft in a four-year-old girl. Issue 3 (3rd May 2020) - Vermeersch, Nicolas; Peters, Benjamin; Somville, Johan; Van Landuyt, Koenraad; Thiessen, Filip; Tondu, Thierry
Abstract: Background: Ewing's sarcoma is the second most common primary malignant bone tumour in children. Depending on localisation and extent, massive bone defects remain when curative surgery is performed. Whereas in the past, limb amputation was often unavoidable to obtain curative resection, nowadays different limb saving reconstructive options are available. Case report: We report the successful reconstruction of a massive femur defect with a free vascularised fibular graft (FVFG) after Ewing's sarcoma resection in a four-year-old girl. Both the age of the patient and the extensive graft hypertrophy makes this case exceptional. Conclusion: Femur reconstruction with a FVFG is a rarely performed and complex procedure in young children. It is an excellent reconstructive technique for large long bone defects, which can avoid limb amputation without compromising oncologic outcome.